Water Use and User Attitudes: Common-Pool Resources and Longitudinal Change in a Brazilian Community. Issue 2 (1st June 2019) - Ditty, John Marr; Totti, Maria Eugênia
Abstract : Common-pool resources (CPRs) are subtractable resources that are physically or institutionally available for many users. The present study sought primary participant observation and focus group data on a Brazilian CPR-dependent community. It analyzes this data through the lens of CPR theory to assess ongoing local natural resource management efforts against longitudinal changes related to large-scale state and private development projects. The findings indicate that real or perceived changes related to the resources, technology, human populations, and decision-making processes in the study area have disrupted social arrangements and resulted in natural resource degradation. The article argues that, in order to achieve sustainability objectives, CPR-guided policy formulation must consider the social embeddedness of community-based actors and resources within their wider historical and social contexts, as well as user attitudes and relations among shifting conditions on multiple scales.